Sistem Kendali dan Monitoring Parameter Limbah Cair Tahu sebagai Larutan Nutrisi Tanaman Hidroponik Bebasis Internet Of Things - Asgia Setya Mardika; Tri Rahajoeningroem (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2021)
Abstract - In the manufacturing process of tofu, tofu produces two kinds of waste, namely solid waste and liquid waste. Tofu liquid waste can be used as liquid organic fertilizer. One way to treat tofu liquid waste is to make liquid organic fertilizer, namely by mixing tofu liquid waste with raw water, acid solution and also alkaline solution so that it can be used as liquid organic fertilizer. This study aims to design and produce a monitoring and control system that is able to produce liquid organic fertilizer for lettuce plants that are cultivated hydroponically with the help of technological engineering. The application of technology in the process of making liquid organic fertilizer and also the fertilization process, one of which is the application of technology based on the Internet of Things (IoT) which can provide important information such as the level of nutritional needs, temperature and pH as a reference for the success of fertilization which can be monitored and controlled for the limits of its needs. at all times. Liquid organic fertilizer produced with the help of a system designed has met the quality standard of liquid organic fertilizer which has a nutrient concentration level with a value range of 810.14 ppm to 839.81 ppm, a temperature value range of 26.28℃ to 27.18℃ and a pH with the range of values ​​is 6.11 to 6.99 where this can be proven by referring to the Decree of the Minister of Agriculture No: 261/KPTS/SR.310/M/4/2019 concerning the minimum technical requirements for organic fertilizer and the regulation of the Minister of the Environment of the Republic of Indonesia No. .5 of 2004 concerning the value of waste quality standards. The result of this system produce lettuce wich has a weight 25 grams and a height of 20 cm. Keyword : Tofu Liquid Waste, Liquid Organic Fertilizer, Internet of Things, Hydroponics, Microcontroller Atmega 2560